(untitled) (Eurasian Journal of Engineering and Technology, 2022)
In this work, the publication of the decree of the Russian emperor of 1916 on mobilization of the inhabitants of the Turkestan territory for labor for work behind the front, and the difficulties in the census, in what order mobilization work should be carried out, and how many people from the regions will be involved in mobilization, the age limit.